Determining the optimal degradation rate of biodegradable films in a maize farmland based on the EWM-TOPSIS model - Wangwang Zhang; Weishu Wang; Yuanzheng Zhang; Fangping Wang; Shijun Sun (Agricultural Water Management)
Biodegradable film is considered a promising alternative to conventional plastic film in agriculture production. Differences in degradation rates result in varying effects on soil temperature and moisture, which directly affect crop growth and yield. However, studies on the effects of biodegradable films with different degradation rates on crop growth remain limited. To investigate these effects, a field experiment was conducted in 2019 and 2020, featuring three biodegradable films with degradation induction periods of 30 days (M1), 60 days (M2) and 90 days (M3), and a non-mulching control (CK). The results indicated that the degradation rates of the three films followed the expected order of M1 > M2 > M3, with final breakage rates of 27.23 %, 23.68 %, and 2.73 % in 2019, and 38.28 %, 28.63 %, and 7.39 % in 2020, respectively. Biodegradable film mulching increased average soil moisture, temperature, and the content of NO3–-N and NH4+-N throughout the entire maize growth period. Due to its fastest degradation rate, M1 exhibited weaker warming and moisture-retention effects compared to M2 and M3. The favorable soil conditions created by biodegradable film mulching promoted maize growth, advanced the peak times of plant height and leaf area index, and increased maize yield. Compared to CK, M1, M2, and M3 increased maize yield by 12.96 %, 14.84 %, and 15.86 % in 2019, and 15.12 %, 16.29 %, and 15.91 % in 2020, respectively. Furthermore, biodegradable film mulching also increased maize water use efficiency and nitrogen partial factor productivity by reducing soil evaporation and increasing maize yield. The EWM-TOPSIS model ranked M2 as the optimal treatment for both years, followed by M1 and M3. This study provides valuable reference for determining biodegradable films with suitable degradation rates in the experimental region.